Hypoglycemic effect of crude water soluble polysaccharide extracted from tubers of purple and yellow water yam (Dioscorea alata L.) on alloxan-induced hyperglycemia Wistar rats - Estiasih, Teti; Umaro, Donny; Harijono, . (Progress in Nutrition, 2018)
This study aimed to examine the ability of crude water soluble polysaccharide (WSP) extracts from yellow and purple water yam tubers in lowering blood glucose level in hyperglycemia condition. Twenty male Wistar strain rats were divided into 4 groups: normal control group, hyperglycemia group administered by crude WSP extract from purple water yam (WSP-P), hyperglycemia group administered by crude WSP extract from yellow water yam (WSP-Y), and control hyperglycemia group. After reaching blood glucose level >200 mg/dL by alloxan induction, crude WSP extract was force fed at dose of 400 mg/kg bw/day in 4 week experiment. The results showed that both crude water yam WSP extracts had hypoglycemic effect. The more pronounce effect was found in crude WSP extract from purple water yam. Fasting blood glucose of rats administered by crude WSP extract gradually decreased. The sharp decline was found in WSP-P group. Crude water yam WSP extract is a fermentable polysaccharide that produced short chain fatty acids (SCFA) with concentration acetate > propionate > butyrate. There was no statistically different of SCFA produced in WSP-P and WSP-Y groups. Administration of crude WSP extract of both water yams is able to prevent body weight loss due to alloxan induction. In conclusion, WSP from purple and yellow water yams exhibited blood glucose lowering properties in hyperglycemia condition. There was a slight different magnitude effect of purple and yellow water yams in decreasing fasting blood glucose. SCFA formation seemed to contribute in improving blood glucose level.